2021
DOI: 10.3233/jad-210042
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Approach of Low-Dose Whole-Brain Ionizing Radiation Treatment in Alzheimer’s Disease Dementia Patients1

Abstract: Our research team recently published two relevant papers. In one study, we have seen the acute effect of low-dose ionizing irradiation (LDIR) did not reduce the amyloid-β (Aβ) protein concentration in brain tissue, yet significantly improved synaptic degeneration and neuronal loss in the hippocampus and cerebral cortex. Surprisingly, in another study, we could see late effect that the LDIR-treated mice showed significantly improved learning and memory skills compared with those in the sham group. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Low-dose radiation (LDR) has been reported to be an effective treatment strategy for AD . We utilized LDR as a positive treatment to compare the difference between AD + LDR and AD + MD + LDR, as well as the groups administered H. pylori .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-dose radiation (LDR) has been reported to be an effective treatment strategy for AD . We utilized LDR as a positive treatment to compare the difference between AD + LDR and AD + MD + LDR, as well as the groups administered H. pylori .…”
Section: Resultsmentioning
confidence: 99%
“…H. pylori was more abundant in both AD and AD + MD human subjects, although other microbiota included Prevotella buccae, Coprococcus catus, Lactobacillus gasseri, and Bif idobacterium lactis, which were significantly reduced in abundance (Supplementary Figure 4A− Low-dose radiation (LDR) has been reported to be an effective treatment strategy for AD. 31 We utilized LDR as a positive treatment to compare the difference between AD + LDR and AD + MD + LDR, as well as the groups administered H. pylori. Figure 4 indicates fasting glucose and HOMA-IR levels increased after administration of H. pylori and decreased after LDR treatment (Figure 4A,B).…”
Section: H Pylori In the Gutmentioning
confidence: 99%
“…However, the authors noted that heterogeneity between exposures and outcome measures made comparisons between cohorts difficult ( Pasqual et al, 2020 , 2021 ). Recent clinical trials are investigating the potential therapeutic effect of ionizing radiation on Alzheimer’s disease pathology but results from such clinical trials in humans have yet to be reported ( Chung et al, 2021 ; Jebelli et al, 2022 ). The evidence for ionizing radiation-induced late neurodegenerative disorders from the Japanese Atomic Bomb Survivors as well as other cohorts with accidental exposures is also mixed.…”
Section: Evidence Base Describing the Impact Of Ionizing Radiation On...mentioning
confidence: 99%
“…9 The primary concerns of the antibody include its inability to reach therapeutic objectives in the studies, and reported integrity difficulties, cost-effectiveness, possible side effects, need for routine observation, and criticism of the "amyloid burst theory". Chung et al 10 suggested low-dose ionizing radiation (LDIR) treatment as a therapy for AD and found that it reduced synapse degradation and loss of neuronal tissue in the frontal cerebrum and hippocampus, increased cognition and memorization abilities contrasted to the group, and enhanced neuronal deterioration. Additionally, the brain tissue was considerably reduced.…”
Section: Literature Surveymentioning
confidence: 99%